Learning a Foreign Language Using Information Technologies for Comfortable Implementation of the Professional Position of a Future Specialist in a Foreign Language Environment - Paltseva, Valentyna; Postolenko, Iryna; Biletska, Iryna; Kmit, Olena; Mykhailenko, Olena; Yatsyna, Svitlana; Kuchai, Tetiana (My University, 2022)
At the present stage, the main directions of the professional position of a specialist in the implementation of English-language Education are to improve and spread the practice of learning languages throughout a person's life by involving information, communication and digital technologies in the educational process. Computerization of the educational process in Higher Education Institutions is considered as one of the first and most promising areas for improving the quality of education in Higher Education Institutions. The necessity of ensuring timely training and retraining of specialists of various profiles (in particular teachers) on the effective use of domestic and foreign electronic resources with the help of modern information technologies for the implementation of the professional position of a future specialist in a foreign-language environment is noted. The main goal of teaching a foreign language (the formation of students' communicative competence, which means mastering the language as a means of intercultural communication) is defined. The types of speech activity that cover the content of teaching a foreign language are highlighted. The main types of assessment in a foreign language are shown – current (non-classroom), thematic, semester, annual assessment and final state certification. The task of the teacher is drawn, which is to create conditions for practical language acquisition for each student, to choose such teaching methods by means of information technologies that would allow each student to show their activity, their creativity; to activate the cognitive activity of the student in the process of learning a foreign language.
Postolenko Iryna Learning a Foreign Language Using Information Technologies for Comfortable Implementation of the Professional Position of a Future Specialist in a Foreign Language Environment / Iryna Postolenko, Iryna Biletska, Olena Kmit, Valentyna Paltseva, Olena Mykhailenko, Svitlana Yatsyna, Tetiana Kuchai // IJCSNS International Journal of Computer Science and Network Security. – 2022. – Vol. 22, № 11. – P. 63-70.
Keywords: information technologies; foreign language; professional position; future specialist; foreign language environment; teacher; communication